Break and Flow : Hip Hop Poetics in the Americas - Hankin, Charlie D., 1989- (Book collections on Project MUSE., 2023)
"Drawing on ethnographic fieldwork and an archive of hundreds of songs by more than sixty hip hop artists, this book examines how rap's political messages are adapted and reinterpreted to reflect the unique situations in Cuba, Brazil, and Haiti"--